2003
DOI: 10.1177/00222194030360040601
|View full text |Cite
|
Sign up to set email alerts
|

Students Classified as LD Who Petitioned for or Fulfilled the College Foreign Language Requirement—Are They Different?

Abstract: This replication study compared 86 petition students who received course substitutions for the college foreign language (FL) requirement with 40 nonpetition students who fulfilled the FL requirement by passing FL courses on cognitive and academic achievement measures and graduating grade point average. The results showed significant differences between the two groups, favoring the nonpetition group on one measure, the American College Testing (ACT) score, when IQ was used as a covariate; however, no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 36 publications
(53 reference statements)
4
28
1
Order By: Relevance
“…Studies with college L2 learners classified as LD have found that students with IQ-achievement discrepancies did not exhibit more severe L1 learning problems or lower L2 aptitude than either LD or other low-achieving students without IQ-achievement discrepancies (Sparks & Javorsky, 1999;Sparks, Philips, Ganschow, & Javorsky, 1999a;Sparks, Philips, & Javorsky, 2002). Also, college students classified as LD who received course substitutions for the L2 requirement (petition) and LD students who fulfilled the college L2 requirement (non-petition) by passing L2 courses did not exhibit significant differences in L1 cognitive ability, L1 achievement, or college entrance scores (i.e., ACT, SAT) (Sparks, Philips, Ganschow, & Javorsky, 1999b; Sparks, Philips, & Javorsky, 2003a).…”
Section: L2 Learners Classified As Ld and Adhdmentioning
confidence: 99%
“…Studies with college L2 learners classified as LD have found that students with IQ-achievement discrepancies did not exhibit more severe L1 learning problems or lower L2 aptitude than either LD or other low-achieving students without IQ-achievement discrepancies (Sparks & Javorsky, 1999;Sparks, Philips, Ganschow, & Javorsky, 1999a;Sparks, Philips, & Javorsky, 2002). Also, college students classified as LD who received course substitutions for the L2 requirement (petition) and LD students who fulfilled the college L2 requirement (non-petition) by passing L2 courses did not exhibit significant differences in L1 cognitive ability, L1 achievement, or college entrance scores (i.e., ACT, SAT) (Sparks, Philips, Ganschow, & Javorsky, 1999b; Sparks, Philips, & Javorsky, 2003a).…”
Section: L2 Learners Classified As Ld and Adhdmentioning
confidence: 99%
“…In their research studies, Sparks and his colleagues have found that diagnosticians and disability service providers may have used students' MLAT scores in a discrepancy analysis to diagnose a disability for foreign language learning and to recommend course substitutions for the foreign language requirement. They have recommended that the MLAT not be used in either of these ways (Sparks, 2001;Sparks, Philips et al, 1999aSparks, Philips, & Javorsky, 2002. In some cases, they have also found that the MLAT has been used as the only testing measure to recommend course substitutions for the foreign language requirement.…”
Section: Using the Mlat To Recommend Course Substitutions/ Waiversmentioning
confidence: 99%
“…In their studies, Sparks et al have found many students who withdrew from foreign language courses before completion; thus, there was no course grade available and the course outcome was unknown. In addition, other students have been granted course substitutions for the foreign language requirement without having enrolled in a foreign language course (see Sparks Q Javorsky, 1999a; Sparks, Philips, et al, 1996;Sparks, Philips, et al, 1999aSparks et al, 2002Sparks et al, , 2003. Furthermore, there is empirical evidence showing that students classified as LD who obtain similar scores on the MLAT (and similar levels of native language skills) achieve different outcomes in foreign language courses; that is, some pass foreign language courses and fulfill the foreign language requirement and others withdraw from or do not enroll in foreign language courses before being granted course substitutions.…”
Section: Misunderstanding the Foreign Language Aptitude Conceptmentioning
confidence: 99%
See 2 more Smart Citations